2014
DOI: 10.1136/thoraxjnl-2014-205587
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled mannitol for non-cystic fibrosis bronchiectasis: a randomised, controlled trial

Abstract: Rationale Bronchiectasis is characterised by excessive production of mucus and pulmonary exacerbations. Inhaled osmotic agents may enhance mucociliary clearance, but few long-term clinical trials have been conducted. Objectives To determine the impact of inhaled mannitol on exacerbation rates in patients with non-cystic fibrosis (CF) bronchiectasis. Secondary endpoints included time to first exacerbation, duration of exacerbations, antibiotic use for exacerbations and quality of life (QOL) (St George's Respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
139
1
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(157 citation statements)
references
References 29 publications
2
139
1
15
Order By: Relevance
“…The study failed to meet its primary end-point, with a rate ratio for exacerbations of 0.92 (95% CI 0.78-1.08; p=0.3). Among secondary endpoints there was an increase in time to next exacerbation and a small improvement in SGRQ with mannitol treatment [56]. Therefore, despite two large trials the role of mannitol in bronchiectasis treatment remains unclear.…”
Section: Inhaled Hyperosmolar Agents and Mucolyticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study failed to meet its primary end-point, with a rate ratio for exacerbations of 0.92 (95% CI 0.78-1.08; p=0.3). Among secondary endpoints there was an increase in time to next exacerbation and a small improvement in SGRQ with mannitol treatment [56]. Therefore, despite two large trials the role of mannitol in bronchiectasis treatment remains unclear.…”
Section: Inhaled Hyperosmolar Agents and Mucolyticsmentioning
confidence: 99%
“…Therefore a further trial was conducted focussing on exacerbations. This study randomised 233 patients to 400 mg inhaled mannitol or control mannitol for 52 weeks [56]. The population was tightly defined, requiring two exacerbations in the previous year, FEV1 between 40 and 85% predicted and a baseline SGRQ score of ⩾30 points [56].…”
Section: Inhaled Hyperosmolar Agents and Mucolyticsmentioning
confidence: 99%
“…This is only achievable with clearer precision medicine approaches for the disease which in turn is reliant on a better mechanistic understanding of its pathology and progression. For instance, several failed clinical trials in bronchiectasis including recombinant DNAase and inhaled dry powder mannitol, both effective therapies in cystic fibrosis (CF), did not translate [13,14]. This illustrates that while the bronchiectasis appears anatomically similar to that in CF, pathophysiological differences exist and probably extend across different aetiologies.…”
mentioning
confidence: 99%
“…The authors concluded however, that therapy needed to be continuous to maintain efficacy [23]. Other recent trials of therapies aiming to reduce exacerbations, such as the non-antibiotic mucoactive inhaled mannitol [24,25], or nebulized antibiotics such as colistin [26], and aztreonam lysine [27] all failed to show significant benefits in their primary end points. This may reflect the choice of end point(s) or the prerequisite study population rather than a true lack of efficacy.…”
Section: Which Competitor Compounds/classes Of Compounds Are In the Cmentioning
confidence: 99%